Chronoeffects of the Herbal Medicines Puerariae radix and Coptidis rhizoma in Mice: A Potential Role of REV-ERBα - Liu, Jinming; Xu, Haiman; Zhang, Li; Wang, Shuai; Lu, Danyi; Chen, Min; Wu, Baojian (Frontiers in Pharmacology, 2021)
Identifying drugs with circadian time-dependent efficacy (chronoefficacy) and understanding the underlying mechanisms would help to improve drug treatment outcome. Here, we aimed to determine chronoefficacy of the herbal medicines Puerariae radix (PR) and Coptidis rhizoma (CR), and investigate a potential role of REV-ERBα as a drug target in generating chronoefficacy. The efficacy of PR against hyperhomocysteinemia in mice was evaluated by measuring total homocysteine, triglyceride levels and lipid accumulation. PR dosed at ZT10 generated a better efficacy against hyperhomocysteinemia than drug dosed at ZT2. Furthermore, PR increased the expressions of REV-ERBα target genes Bhmt, Cbs and Cth (encoding three key enzymes responsible for homocysteine catabolism), thereby alleviating hyperhomocysteinemia in mice. Moreover, CR attenuated chronic colitis in mice in a circadian time-dependent manner based on measurements of disease activity index, colon length, malondialdehyde/myeloperoxidase activities and IL-1β/IL-6 levels. ZT10 dosing generated a better anti-colitis efficacy as compared to ZT2 dosing. This was accompanied by lower production of colonic inflammatory cytokines (i.e., Nlrp3, IL-1β, IL-6, Tnf-α and Ccl2, REV-ERBα target genes) in colitis mice at ZT10 dosing. The circadian patterns of PR and CR effects were respectively consistent with those of puerarin (a main active constituent of PR, a REV-ERBα antagonist) and berberine (a main active constituent of CR, a REV-ERBα agonist). In conclusion, the therapeutic effects of PR and CR depend on dosing time in mice, which are probably attributed to circadian expression of REV-ERBα as the drug target. Our findings have implications for improving therapeutic outcomes of herbal medicines with a chronotherapeutics approach.